Methodological aspects of formation and strategic development of a business model of small business - A. E. Vostroknutov; V. I. Loyko (Новые технологии)
The article substantiates the need to develop a method for the formation and strategic development of a business model for small business organizations and a comparative analysis of the existing methodological approaches has been carried out. As a result, basic methods (A. Osterwalder's approach, SWOT-analysis and the method of constructing a strategic map) have been selected and a block diagram of the proposed method developed.